Aplikasi Spotify: Solusi Baru dalam Pembelajaran Menulis Cerpen di SMA - Hasan, Jihan Septiani; Lubis, Fitriani (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The purposes of this study (1) to describe the ability of writing short storiy for XI grade students of SMA Negeri 6 Medan by applying the Spotify application as a learning medium; (2) tp describe the ability to writing short story for XI grade students of SMA Negeri 6 Medan without applying the Spotify application as a learning medium; (3) to describe the effect of applying the Spotify application as a learning medium on the ability to write short story texts for XI grade students of SMA Negeri 6 Medan. The research method used is an experimental method with a posttest-only for control design. The results showed: (1) the class mean using the Spotify application was 82.2 with a standard deviation of 11.51347 (2) the class mean without applying the Spotify application was 54.8 with a standard deviation of 21.43725 (3) The results of the calculation of the hypothesis test obtained tcount = 6.699 and ttable = 1.667. Ha's conclusion is accepted, namely tcount > ttable, meaning that there is a positive influence on the application of the Spotify application as a medium for learning. The Spotify application can be used as an alternative learning media, especially literature, because: (1) it increases the enthusiasm of students in arguing in determining the building elements of short story texts that are heard from podcasts, (2) it becomes reference for students regarding short stories and figure of speech themes, which are in Spotify (3) it can train students' listening skills, because the process of Spotify media learns while listening.